Evaluation of Instructor's Perssuasive Communication Skill in Anti Bullying Law Explanation Program - Angelika Putri Ariyani; Agus Naryoso, S.Sos, M.Si (Interaksi Online, 2017)
Many bullying cases that happened in Indonesia, especially in Semarang City, became the background of this Penerangan Hukum Jaksa Masuk Sekolah Program with the theme of Anti Bullying. The program is expected to be able to change student’s behavior not to do bullying actions and aware of the law applied in Indonesia towards bullying actions performed. The purpose of the program will be achieved if the instructor team has a good persuasive communication ability. Persuasive communication ability can be measured through evaluation activities held by Kejaksaan Tinggi Jawa Tengah, but in fact to achive the purpose of the program, Law Explanation Team (Tim Penerangan Hukum) has not do any evalution yet about persuasive communication that has been done. The research which aimed to evaluates the persuasive communication level of the instructors of anti bullying law explanation program uses quantitative and qualitative approach with pragmatic paradigm to help spells out the evalution results. The research with quantitative approach aimed to 167 respondents which are the audience of anti bullying law explanation program, and the research with qualitative approach aimed to 3 interviewees which are law explanation team of Kejaksaan Tinggi Jawa Tengah. The result of the research shows that instructor’s persuasive communication ability level based on inventio, dispositio aspects and instructor’s attractiveness development aspect are good, but the purpose to put on the anti bullying manner did not achieved. The knowledge of the audience are very low considering the material given, although the audience’s affection to the program are very good, so that the audiences still do bullying. Penerangan hukum jaksa masuk sekolah team already prepare the materials well, know the characteristics of the audience, choosing a good method, and also organize verbal and non verbal message well, supported by power point the team has. The team is also good in building audience’s interest, but the communication happened was not effective due to many bullying actions that still performed. Anti bullying law explanation program that has been done once in a school could not support persuasive communication in putting on anti bullying manner. It needs a continous activities to achieve the persuasive communication.